种在石墨烯表面吸附水解聚酰亚胺分子来提高比电容的方法 (2018)
本发明属于高储能石墨烯基超级电容器的电极材料制备领域。由于石墨烯大的比表面积和高的电子迁移率等优点，使石墨烯成为种理想的电容材料。但由于石墨烯片层易于堆叠团聚，溶剂中分散性不好和含氧官能团还原不彻底等原因，大大减小了石墨烯的实际比电容。本发明首次用定质量比的液晶氧化石墨烯/碳酸铵/氯化钠/CVD石墨烯的均匀分散液直接滴入尺寸可控的聚四氟乙烯模具内，刮平干燥成膜，随后在定浓度的氨水和聚酰亚胺溶液中水热还原，随后进行低温加热的方法制备高比电容的氮掺杂石墨烯薄膜电极材料。此发明着重于大规模和低成本制备高储能石墨烯，提高石墨烯基超级电容器的比电容和能量密度，进而促进石墨烯基超级电容器的商业化应用。 The invention belongs to the preparation field of an electrode material of a high-energy-storage graphene-based supercapacitor. Based on the advantages of large specific surface area, high electron mobility and the like of graphene, the graphene becomes an ideal capacitor material; however, the actual specific capacitance of graphene is greatly lowered caused by high probability of stacking and agglomeration of graphene laminated layers, low dispersity in a solvent, incomplete reduction of an oxygen-containing functional group and the like. A uniform dispersion solution of liquid crystal graphene oxide/ammonium carbonate/sodium chloride/CVD graphene at certain mass ratio is dropped in a polytetrafluoroethylene die w